Langerhans Cells Of The Human Skin Possess High-affinity 12(s)-hydroxyeicosa Tetraenoic Acid Receptors - Arenberger P (EUROPEAN JOURNAL OF IMMUNOLOGY, 1992)
The arachidonic acid metabolite 12-hydroxyeicosatetraenoic acid (12-HETE) is the main eicosanoid formed by epidermal cells and is assumed to play an important role in skin physiology and pathophysiology. Our aim was to find out whether epidermal Langerhans cells possess specific receptors for 12-HETE which would mediate the effects of this eicosanoid in their skin microenvironment. By radioligand binding studies on isolated human Langerhans cells, we could identify specific binding sites for 12(S)-HETE. The analysis of binding data revealed a single class of binding sites with a K(d) of 3.32 +/- 0.45 nm and a B(max) of 691 000 +/- 58 000 receptors per cell.The binding was saturable, readily reversible, and specific for 12(S)-HETE. The receptor is likely to mediate the potent chemotactic response of human Langerhans cells towards 12(S)-HETE, which we previously described. Our results strongly suggest that extremely low concentrations of 12-HETE which is formed by epidermal keratinocytes may dramatically influence the biology of Langerhans cells by receptor-mediated effects.